Cooperation on the Nile : Bringing Down the Glass Wall - World Bank Group (World Bank, Entebbe, 2016)
A unique cooperation program, working across different countries with varying national interests, stakeholders, and projects, has brought down the glass wall. Coordinated by the Nile Basin Initiative (NBI), this program has successfully built trust, strengthened capacity, and created an enabling environment for sustainable and equitable development of the Nile Basin water resources. Transboundary cooperation has advanced regional integration through identifying and developing joint investments. This note presents the journey so far by the Nile Basin member states in building regional cooperation, and the crucial role played by the NBI in the achievement.